Perception of prevention of Japanese Encephalitis with emphasis on its vaccination programme: a community based study in a slum of Kolkata - Dasgupta Aparajita; Dey Atanu; Paul Bobby; Bandyopadhyay Lina; Garg Shobhit (Jabatan Kesihatan Masyarakat, Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Introduction Japanese Encephalitis (JE) is a mosquito borne disease with epidemic potential. There is no specific treatment available till date and apart from vector control, vaccination of individuals is considered as a safe and effective measure for prevention. Vaccination campaign among 1-15 years is being carried out with full vigour from 2015 onwards in West Bengal. Objectives This study was conducted to assess the knowledge of the care givers of 1-15 years old children about JE and its prevention and to find out the factors associated with vaccination status of the children. Methods A cross sectional, community based study was conducted from May-June 2016 in a slum of Chetla, Kolkata, which is within the service area of Urban Health Unit and Training Centre (UHU&TC), Chetla of All India Institute of Hygiene and Public Health, Kolkata, where the campaign prior to the study was completed in March 2016. Care givers of 90 children of aged 1-15 years were interviewed with a pre-designed, pre-tested, structured schedule. Results Mean age of the surveyed children was 6.34 years (SD 3.76) and 88% of them were vaccinated during the campaign. 56.7% of the caregivers had poor knowledge about JE and 84.95% were sensitized about the campaign by relatives/friends followed by health workers (33.7%). Low socio-economic status and good knowledge of JE had significant association with vaccination of the child after adjusting with other factors (age and sex of the child, education and occupation of parents, type of family). Conclusions Enhancement of knowledge and awareness about JE with appropriate health education programmes and special emphasis on sensitization campaigns for JE vaccination at both mass and individual level would prevent emergence of JE epidemics in future.